Taxpayer Compliance at KPP Pratama Surabaya Mulyorejo with Risk Preference as A Moderated Variables - Yanto, Alif Faruqi Febri; Pranoto, Soeparlan; Suhartini, Dwi (Universitas Pamulang, 2021)
This study aims to examine taxpayer compliance that is influenced by tax audits, knowledge of taxation and tax administration services moderated by risk preferences. The object in this study is an individual taxpayer registered at KPP Pratama Surabaya Mulyorejo. The analytical method used in this study is GSCA. The results showed that tax audits, fiscal services have an effect on taxpayer compliance, while tax knowledge does not contribute to taxpayer compliance. Risk preference moderates the relationship between tax audit and taxpayer services on taxpayer compliance, but cannot moderate taxation knowledge on taxpayer compliance.